2015
DOI: 10.1097/qad.0000000000000783
|View full text |Cite
|
Sign up to set email alerts
|

Growth reconstitution following antiretroviral therapy and nutritional supplementation

Abstract: Objective As antiretroviral treatment (ART) expands for HIV-infected children, it is important to determine its impact on growth. We quantify growth and its determinants following ART in resource-limited (RLS) and developed settings (DS). Design Systematic review and meta-analysis. Methods We searched publications reporting growth [weight-for-age (WAZ), height-for-age (HAZ), and weight-for-height (WHZ) Z-scores] in HIV-infected children following ART through August 2014. Inclusion criteria: 1) <18 years; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 77 publications
3
35
0
Order By: Relevance
“…In our cohort, late age at ART initiation was strongly associated with stunting and poor HAZ evolution. This finding has been observed in many other studies, but mostly among children younger than age 10 years . Children who spend their first years of life with HIV without ART may have chronic inflammation due to uncontrolled HIV, which can affect growth.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In our cohort, late age at ART initiation was strongly associated with stunting and poor HAZ evolution. This finding has been observed in many other studies, but mostly among children younger than age 10 years . Children who spend their first years of life with HIV without ART may have chronic inflammation due to uncontrolled HIV, which can affect growth.…”
Section: Discussionsupporting
confidence: 79%
“…Delayed pubertal onset is also observed in the general population in LMICs [41], and may reflect poor nutrition during the first 1000 days of life and in later childhood [42], which is often the case for children with HIV [22]. In rural villages of The Gambia, HAZ evolution was described from birth to 30 years and showed similar patterns to our study, with an apparent decline at the start of adolescence, especially for males, which could be explained by high rates of stunting during infancy and a later entry into puberty compared to the UK reference population [43].…”
Section: Discussionmentioning
confidence: 99%
“…Both malnutrition and stunting are common among children and adolescents living with HIV in LMICs, with prevalence estimated as high as 42% and 73%, respectively [10*,7376]. Malnutrition during the first year of life is associated with decreased lung function at one year of age [52*].…”
Section: Risk Factors For Hiv-associated Chronic Lung Disease Among Amentioning
confidence: 99%
“…WAZ is considered to be a marker of recent nutritional insult, while low HAZ reflects chronic issues of health and nutrition (20). Studies have shown variable recovery of height after initiating ART (21). Kabue et al reported improvement in HAZ at 1 year (p<0.05)(22); Mwiru et al (2014) likewise found improvement in HAZ, but children's HAZ scores never normalized despite catch-up growth (14).…”
Section: Discussionmentioning
confidence: 99%
“…While this reflects standard local practice and adds to generalizability of our results, it limits our analytical ability to evaluate and adjust for supplementation as a factor in growth improvement. Several studies have demonstrated positive effects from supplementation, but there is a need for additional research (21). …”
Section: Discussionmentioning
confidence: 99%